From newspapers to FYP an analysis of Philippine print newsrooms’ motivations behind TikTok reportage on Philippine Offshore Gaming Operators (POGOs) in 2024 - Buenaflor, Cyril G.
With the notable shift of information-seeking from users, Philippine print newsrooms ventured into adapting TikTok for reporting. Using Vroom’s Expectancy Model, this study explores the motivations and strategies of the selected print newsrooms in TikTok reporting, particularly covering Philippine Offshore Gaming Operators (POGOs). This research analyzed POGO-related TikTok videos produced by three print newsrooms, the Manila Bulletin, Manila Times, and the Philippine Star. A content analysis of their POGO-related TikTok videos revealed that newsrooms leaned towards staying in traditional reporting, despite TikTok’s distinct culture and logic. Among the three newsrooms, only the Philippine Star was found to be motivated with its high level of expectancy, instrumentality, and valence, due to their effort in aligning content on TikTok’s logic, such as incorporating unique music. Through semi-structured interviews, the study found that the general motivation of these newsrooms was to reach a younger audience. For social media representatives of these print newsrooms, they highlighted the need to penetrate the platform, especially with the continuous and rampant disinformation on the platform. This research established that TikTok reporting requires the platform’s design, such as short-form video, conversational, and entertaining.